Gênero e Sexualidade para Iniciantes - Rodrigues, Gislene Oliveira; Camargo, Wagner Xavier (Revista de Ciências Sociais, 2018)
Resenha de Jaimee Garbacik. Gender & Sexuality for beginners. Danbury: For Beginners LLC. 2013. 217 pp.